Elevated Serum Uric Acid/Albumin Ratio as a Predictor of Post-Contrast Acute Kidney Injury After Percutaneous Coronary Intervention in Patients with ST-Segment Elevation Myocardial Infarction - Zhang Y; Xu Z; He W; Lin Z; Liu Y; Dai Y; Chen W; Chen W; He W; Duan C; He P; Liu Y; et al. (Dove Medical Press, 2022)
Yeshen Zhang,1,2,* Zhengrong Xu,3,* Wenfei He,4,* Zehuo Lin,1,2 Yaoxin Liu,1,2 Yining Dai,1,2 Wei Chen,5 Weikun Chen,1,2 Wenlong He,1,2 Chongyang Duan,6 Pengcheng He,1,2 Yuanhui Liu,1,2 Ning Tan1,2 1Department of Cardiology, Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, People's Republic of China; 2Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, People's Republic of China; 3Department of Cardiology, People's Hospital of Baoan Shenzhen, Guangzhou, People's Republic of China; 4Department of Cardiology, Guangdong Provincial People's Hospital's Nanhai Hospital, the Second People's Hospital of Nanhai District Foshan City, Foshan, People's Republic of China; 5Department of Cardiology, Fujian Provincial Clinical College of Fujian Medical University, Fujian Provincial Hospital, Fujian Institute of Cardiovascular Disease, Fuzhou, People's Republic of China; 6Department of Biostatistics, School of Public Health, Southern Medical University, Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Ning Tan; Yuanhui Liu, Department of Cardiology, Guangdong Cardiovascular Institute, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China, Tel +86-20-83819161, Fax +86-20-83824369, Email gdtanning@126.com; liuyuanhui@gdph.org.cnBackground: The serum uric acid/albumin ratio (sUAR), a novel inflammatory marker, effectively predicts acute kidney injury (AKI) and cardiovascular outcomes. However, whether the sUAR predicts post-contrast acute kidney injury (PC-AKI) in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) remains uncertain. In this study, we evaluated the association between the sUAR and PC-AKI in patients with STEMI undergoing PCI.Methods: We consecutively recruited patients with STEMI who underwent PCI and stratified them into three groups according to the terciles of the sUAR. The primary outcome was the incidence of PC-AKI. The association between the sUAR and PC-AKI was assessed by multivariate logistic regression analysis.Results: A total of 2861 patients with STEMI were included in this study. The incidence of PC-AKI increased stepwise with increasing sUAR tercile (2.6% vs 4.0% vs 11.6%, p < 0.001), and the incidence of in-hospital major adverse clinical events (MACEs) was highest among patients in the Q3 group. Multivariate logistic regression analysis revealed that the sUAR was also an independent predictor of PC-AKI (continuous sUAR, per 1-unit increase, odds ratio [OR] [95% confidence interval (CI)]: 1.06 [1.02- 1.10], p = 0.005; tercile of sUAR, OR [95% CI] for Q2 and Q3: 1.18 [0.69- 2.01] and 1.85 [1.12- 3.06], respectively, with Q1 as a reference) but not in-hospital MACEs. In the receiver operating characteristic (ROC) analysis, the area under the curve (AUC) of the sUAR for predicting PC-AKI was 0.708 (95% CI: 0.666- 0.751), and ROC analysis also showed that the sUAR was superior to uric acid and albumin alone in predicting PC-AKI.Conclusion: Increasing sUAR was significantly associated with a higher risk of PC-AKI but not in-hospital MACEs in patients with STEMI who underwent PCI, suggesting that sUAR had a predictive value for PC-AKI after PCI in patients with STEMI. Further studies are required to confirm this finding.Keywords: serum uric acid/albumin ratio, post-contrast acute kidney injury, ST-segment elevation myocardial infarction